Magnetic brain stimulation using iron oxide nanoparticle-mediated selective treatment of the left prelimbic cortex as a novel strategy to rapidly improve depressive-like symptoms in mice - Lu, Qing-Bo; Sun, Jian-Fei; Yang, Qu-Yang; Cai, Wen-Wen; Xia, Meng-Qin; Wu, Fang-Fang; Gu, Ning; Zhang, Zhi-Jun (Dōngwùxué yánjiū, 2020)
Magnetic brain stimulation has greatly contributed to the advancement of neuroscience. However, challenges remain in the power of penetration and precision of magnetic stimulation, especially in small animals. Here, a novel combined magnetic stimulation system (c-MSS) was established for brain stimulation in mice. The c-MSS uses a mild magnetic pulse sequence and injection of superparamagnetic iron oxide (SPIO) nanodrugs to elevate local cortical susceptibility. After imaging of the SPIO nanoparticles in the left prelimbic (PrL) cortex in mice, we determined their safety and physical characteristics. Depressive-like behavior was established in mice using a chronic unpredictable mild stress (CUMS) model. SPIO nanodrugs were then delivered precisely to the left PrL cortex using injection. A 0.1 T magnetic field (adjustable frequency) was used for magnetic stimulation (5 min/session, two sessions daily). Biomarkers representing therapeutic effects were measured before and after c-MSS intervention. Results showed that c-MSS rapidly improved depressive-like symptoms in CUMS mice after stimulation with a 10 Hz field for 5 d, combined with increased brain-derived neurotrophic factor (BDNF) and inactivation of hypothalamic-pituitary-adrenal (HPA) axis function, which enhanced neuronal activity due to SPIO nanoparticle-mediated effects. The c-MSS was safe and effective, representing a novel approach in the selective stimulation of arbitrary cortical targets in small animals, playing a bioelectric role in neural circuit regulation, including antidepressant effects in CUMS mice. This expands the potential applications of magnetic stimulation and progresses brain research towards clinical application.